Integrating Mathematics, Community, Culture, and Place: A Conceptual Framework for Instructional Design - Muliawan Firdaus; Andrea Arifsyah Nasution (JETL (Journal of Education, Teaching and Learning), 2023)
This study proposes a novel instructional design framework that intertwines mathematical concepts with elements of community, culture, and place. The aim is to enhance student engagement and understanding of mathematics by making learning more culturally responsive and contextually relevant. Employing a mixed-methods approach involving teacher interviews, classroom observations, pre- and post-intervention surveys and tests, the study examines the potential benefits of this integrated approach along with its practical challenges. Results indicate that despite initial difficulties in implementation such as time constraints or parental resistance to non-traditional teaching methods, many teachers reported improved student involvement and comprehension when classes were connected to local communities or cultures. Importantly, the study found no significant main effects or interaction effects for grade level or ethnicity on both engagement and understanding scores pre-and post-intervention. This suggests that this instructional model can be equally effective across diverse student populations thereby potentially reducing disparities in mathematical achievement. The findings highlight the potential advantages of an inclusive pedagogical strategy in enhancing mathematics education while acknowledging further research is needed to confirm these results across different settings.